Exploring the Dynamics of Eye Fluid: Lymphatics, Aqueous Humor, and Intraocular Pressure - Maya Sharma (Emerging Trends in Personalized Medicines, 2025)
Lymphatic vessels are essential for regulating interstitial fluid balance, facilitating immune cell transport, supporting lipid absorption, and playing significant roles in tumor development and metastasis. Recent findings have expanded their recognized functions, particularly in pathological contexts. One notable discovery is the involvement of lymphatics in draining aqueous humor from the eye, a process closely linked to the regulation of intraocular pressure (IOP) and its implications for glaucoma progression. This review provides an overview of the dynamics of ocular fluids, examines the distribution and structure of ocular lymphatics, and highlights studies that have advanced the three-dimensional visualization of the ocular vasculature. Additionally, it explores the molecular mechanisms governing the development of ocular lymphatic vessels and investigates how lymphatic pathways may influence aqueous humor outflow. The interaction between lymphatic and glymphatic systems is also discussed, particularly in relation to retinal clearance and diseases affecting the posterior eye. The review concludes by addressing unresolved questions and suggesting research directions to further elucidate the interplay between these systems in maintaining ocular fluid homeostasis.
Keywords: Glaucoma; Intraocular pressure; Lymphatic vessels; aqueous humor drainage; eye disease; lymphatic system